2006
DOI: 10.4028/www.scientific.net/kem.309-311.1311
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of Porous Hydroxyapatite/Poly D/L-lactide Composite for Bone Substitutes and Scaffolds

Abstract: We had investigated the biocompatibility, osteoconductivity, and biodegradability of a porous composite of hydroxyapatite (HA) and poly-DL-lactide (PDLLA) implanted into rabbit femoral condyles. It showed excellent osteoconductivity and biodegradability as a bone substitute. Newly formed bones were remodeled, and materials were resorbed almost completely at 78weeks after implantation. In consideration of its biocompatibility and degradability, we investigated its potential for use as a cellular scaffold and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…This is useful in the context of irregular bone reformation in maxillofacial surgery. According to Hasegawa et al [ 6 , 11 ], porous 3D-HA/PDLLA biomaterial resorbs much more rapidly than HA or β-TCP. This is very important for bone formation, where Chazono et al [ 46 ] previously reported that bone formation occurred after biomaterial resorption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is useful in the context of irregular bone reformation in maxillofacial surgery. According to Hasegawa et al [ 6 , 11 ], porous 3D-HA/PDLLA biomaterial resorbs much more rapidly than HA or β-TCP. This is very important for bone formation, where Chazono et al [ 46 ] previously reported that bone formation occurred after biomaterial resorption.…”
Section: Discussionmentioning
confidence: 99%
“…The pores of the 3D-HA/PDLLA composite are interconnected with an average interconnective pore diameter of 62 μm. The 3D-HA/PDLLA biomaterial was composed of 70 wt% uncalcined and unsintered HA (u-HA) and 30 wt% PDLLA matrix, with 4.1 ± 0.4 MPa compressive strength (viscosity-average molecular weight (Mv): 77 kDa; dextrorotatory-lactide acid/levorotatory-lactide acid ( d / l ) = 50/50 mol%) and without immediate collapse after breaking [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ключевые слова: пористые гидрогели, поливинилпирролидон, наночастицы серебра, гидроксиаппатит, бактерицидные и фунгицидные свойства DOI: 10.15587/1729-4061.2014.27701 кісткової тканини внаслідок різних хірургічних втручань, проведення імплантологічного лікування, а також різних кістково пластичних операцій [3]. Для вирішення цих проблем переважно застосовують ся різні вітчизняні і зарубіжні препарати, створені на основі гідроксіапатиту та трикальційфосфату, що містять хімічні елементи в таких же йонних формах, в яких вони знаходяться в живому організмі [4,5].…”
Section: исследованы закономерности получения наполненных гидроксиаппunclassified
“…3D-HA/PDLLA has been successfully implanted into animal femora and tibia [ 8 , 9 , 10 ]. Moreover, ectopic osteogenesis was observed in the implantation of 3D-HA/PDLLA loaded with bone marrow cells into muscles [ 11 ]. Therefore, it could potentially be developed for clinical applications as a novel bioresorbable scaffold in maxillofacial surgery.…”
Section: Introductionmentioning
confidence: 99%